Análise de um ecossistema de vegetação mista na baixada cuiabana em área de influência de torre micrometeorológica à luz da teoria da escala metabólica - Moretti, Roberta Lima (2021)
The Metabolic Scale Theory (MET) is one of the most general models in ecology and can be used to link physical properties of forests, such as biomass, to ecological processes, such as ecosystem metabolism. TEM is based on assumptions about size distribution, describing the relationship between these sizes with a power law that holds for parts of individuals - leaves, branches and trunks - as well as for the ecosystem - tree height distribution, for example. For ecosystems, TEM states that the specific scale exponent of the power law that relates metabolism to ecosystem mass is α=0.6. The theory for an ecosystem of the cerrado campo sujo type was tested using two different types of routines. To estimate metabolism and biomass and test the fit of the data to TEM, 3 years of EC and EVI data were used in a campo sujo ecosystem. The adjustments obtained for the dry and rainy seasons, as well as the growth and nongrowth of vegetation were analyzed and contrasted. The theoretical allometric scale exponent (α=2/3) was compared with the one that best represents the data analyzed in this work (α=5). Then, environmental variables and energy metrics were used to explain the deviation from theoretical expectations. The allometric coefficient predicted by TEM is statistically compatible with the data collected, however, it cannot be said that this is the value of the coefficient that best represents the relationship between metabolism and ecosystem biomass, since there is compatibility for a wide spectrum of values. It is indicated that the inclusion of water availability and vegetation phenology factors can contribute to the advancement of MET applied to ecosystems.